2014
DOI: 10.1088/0004-637x/794/1/86
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical Instability of White Dwarfs and Breaking of Spherical Symmetry Under the Presence of Extreme Magnetic Fields

Abstract: Massive, highly magnetized white dwarfs with fields up to 10 9 G have been observed and theoretically used for the description of a variety of astrophysical phenomena. Ultramagnetized white dwarfs with uniform interior fields up to 10 18 G, have been recently purported to obey a new maximum mass limit, M max ≈ 2.58 M ⊙ , which largely overcomes the traditional Chandrasekhar value, M Ch ≈ 1.44 M ⊙ . Such a much larger limit would make these astrophysical objects viable candidates for the explanation of the supe… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
62
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 53 publications
(64 citation statements)
references
References 49 publications
2
62
0
Order By: Relevance
“…It was shown by Chandrasekhar & Fermi (1953) that the figure of equilibrium of an incompressible fluid sphere with an internal uniform magnetic field that matches an external dipole field, is not represented by a sphere. The star becomes oblate by contracting along the axis of symmetry, namely along the direction of the magnetic field (see, e.g., Coelho et al 2014). Thus, we consider that the fluid sphere is deformed in such a way that the equation of the ellipticity arising from the magnetic field is given by (Bonazzola & Gourgoulhon 1996;Konno et al 2000;Regimbau & de Freitas Pacheco 2006)…”
Section: Ellipticity Of Magnetized Starsmentioning
confidence: 99%
“…It was shown by Chandrasekhar & Fermi (1953) that the figure of equilibrium of an incompressible fluid sphere with an internal uniform magnetic field that matches an external dipole field, is not represented by a sphere. The star becomes oblate by contracting along the axis of symmetry, namely along the direction of the magnetic field (see, e.g., Coelho et al 2014). Thus, we consider that the fluid sphere is deformed in such a way that the equation of the ellipticity arising from the magnetic field is given by (Bonazzola & Gourgoulhon 1996;Konno et al 2000;Regimbau & de Freitas Pacheco 2006)…”
Section: Ellipticity Of Magnetized Starsmentioning
confidence: 99%
“…A more detailed study about the Super-Chandrasekhar white dwarfs can be found in Ref. 9 , where we showed that several macro and micro physical aspects such as gravitational, dynamical stability, breaking of spherical symmetry, general relativity, inverse β-decay, and pycnonuclear fusion reactions are of most relevance for the self-consistent description of the structure and assessment of stability of these objects.…”
Section: Results and Conclusionmentioning
confidence: 77%
“…As discussed in Ref. 9 , the hypothetic presence of such large magnetic field would contribute to the gravitational mass of the star leading to m B 25M for the case of the maximum magnetic field considered. Finally, it is important to stress, that the M − R relation of these strongly magnetized white dwarfs obtained in Ref.…”
Section: Introductionmentioning
confidence: 83%
“…The properties of Fermionic matter have been intensively studied already many decades ago 1 . Recent astrophysical observations have renewed enormous interest in this subject matter [2][3][4] . For instance, it has been suggested that strongly magnetized white dwarfs (SMWDs) with masses greater than the Chandrasekhar mass limit of 1.4 solar masses may be the progenitors of overluminous type-Ia supernovae 2 .…”
Section: Electron Gases In Strong Magnetic Fieldsmentioning
confidence: 99%